2010
DOI: 10.3390/ijms11103748
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Y Promotes Growth and Adhesion of Ovarian Carcinoma-Derived RMG-I Cells by Upregulating Growth Factors

Abstract: Lewis y (LeY) antigen is a difucosylated oligosaccharide carried by glycoconjugates on the cell surface. Overexpression of LeY is frequently observed in epithelial-derived cancers and has been correlated to the pathological staging and prognosis. However, the effects of LeY on ovarian cancer are not yet clear. Previously, we transfected the ovarian cancer cell line RMG-I with the α1,2-fucosyltransferase gene to obtain stable transfectants, RMG-I-H, that highly express LeY. In the present study, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…And Lewis y could regulate the transforming growth factor β pathway and up-regulate growth factors in ovarian cancer [18,19]. However, in our previous studies, we demonstrated that the over-expression of Lewis y was closely related to the enhancement of the proliferation, drug resistance (including docetaxel-resistance) and metastasis of ovarian cancer [18][19][20]. Besides, we proved that Lewis y inhibited the apoptosis of ovarian cancer [18,19].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…And Lewis y could regulate the transforming growth factor β pathway and up-regulate growth factors in ovarian cancer [18,19]. However, in our previous studies, we demonstrated that the over-expression of Lewis y was closely related to the enhancement of the proliferation, drug resistance (including docetaxel-resistance) and metastasis of ovarian cancer [18][19][20]. Besides, we proved that Lewis y inhibited the apoptosis of ovarian cancer [18,19].…”
Section: Discussionmentioning
confidence: 77%
“…It was also reported that Lewis y could regulate cell cycle related factors via ERK and Akt signaling pathways in ovarian cancer [17]. And Lewis y could regulate the transforming growth factor β pathway and up-regulate growth factors in ovarian cancer [18,19]. However, in our previous studies, we demonstrated that the over-expression of Lewis y was closely related to the enhancement of the proliferation, drug resistance (including docetaxel-resistance) and metastasis of ovarian cancer [18][19][20].…”
Section: Discussionmentioning
confidence: 78%
“…The present study was an exploratory study with a very specific setting providing an early idea about immediate in vivo effects against malign tumor cells in patients. As a [41] that LeY also plays an essential role in ovarian cancer. Additionally, further studies may help select favourable tumor entities by examinations on differences in cell promoting effect if LeY is expressed as part of Her2/neu in contrast to expression of LeY on other backbone structures or expressed as soluble LeY [42].…”
Section: Discussionmentioning
confidence: 99%
“…Our studies showed that, compared with cells without transfection, RMG-I-H cells have enhanced malignant behavior, a shorter cell cycle, and increased resistance to 5-fluorouracil (5,7,8). In addition, LeY mAb dramatically inhibits cell proliferation and cell adhesion of RMG-I-H cells in vitro , and the size and weight of tumors derived from RMG-I-H cells in vivo are reduced significantly by preincubation of RMG-I-H cells with anti-LeY mAb (8,9). All these suggest that LeY is involved in the changes in biological behavior of the RMG-I cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among the genes with modified expression, TGFBI (GenBank ID: BC000097) was significantly up-regulated (11). By immunohistochemical staining and Western blot analysis, we examined the expression of TGF-β1 in nude mouse xenograft tumors and found an increased expression in RMG-I-H cells (9). Because LeY is present on cell surface and may modify the growth factor receptor (12,13), we therefore hypothesized that LeY may be involved in the regulation of TGF-β mediated cell growth as part of TGF-β receptors (TβRs).…”
Section: Introductionmentioning
confidence: 99%